Pupal chaetotaxy of the common mosquitoes of Dacca. - Ameen, M. U.; Talukdar, M. Z. I. (Contributions to Entomology = Beiträge zur Entomologie, 1974)
The history of nomenclature of the pupal chetotaxy of mosquitoes has been reviewed. The chaetotaxy of 5 species of the genus Anopheles, viz., A. vagus, A. supictus, A. annularis, A. hyrcanus var. nigerismus and A. barbirostris, has been described and illustrated.